Dimensi Positif Rumah Tangga pada Pernikahan dini dalam Prinsip Sakinah: Positive Dimensions of Early Marriage Households within the Principle of Sakinah - Novalia, Alya Azmi; Sasmito , Seno Aris (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study aims to analyze the positive dimensions of early marriage households within the principle of sakinah through a case study in Jaya Bhakti Village. Early marriage is generally associated with emotional and economic vulnerability; however, in certain social contexts it may demonstrate positive family resilience. This research employs an empirical field approach through interviews with young couples, religious leaders, and village officials. The findings reveal that young couples are able to build household resilience through clear role distribution, open communication, and strong family and social support. The principle of sakinah functions as a spiritual foundation that guides couples in patience, mutual understanding, and adaptation. Additionally, the decision to delay childbirth due to economic considerations reflects rational family planning and psychological maturity. The study concludes that early marriage can lead to a harmonious household when supported by responsibility, religious guidance, and a constructive social environment.